PENGARUH TINGKAT PENGANGGURAN DAN INDEKS PEMBANGUNAN MANUSIA (IPM) TERHADAP JUMLAH PENDUDUK MISKIN DI PROVINSI SUMATERA UTARA TAHUN 2009-2023 - Ainun Saskia; Joko Suharianto (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study examines the relationship between unemployment rate, Human Development Index (HDI), and poverty levels in North Sumatra Province during the period 2009–2023. Poverty remains a multidimensional issue influenced by various socio-economic factors, including labor market conditions and human development quality. The objective of this research is to analyze both the partial and simultaneous effects of unemployment and HDI on the number of poor people. This study employs a quantitative approach using time series secondary data obtained from official statistical publications. The analysis is conducted using multiple linear regression with Ordinary Least Squares (OLS) method, supported by classical assumption tests to ensure model validity. The findings indicate that the unemployment rate has a positive but statistically insignificant effect on poverty, suggesting that unemployment does not directly determine poverty levels in the observed period. In contrast, HDI shows a negative and statistically significant effect on poverty, implying that improvements in education, health, and living standards effectively reduce poverty. Simultaneously, both variables significantly influence poverty, with the model explaining a substantial proportion of variation. These results highlight the dominant role of human development in poverty reduction and suggest that policies focusing on improving human capital are more effective than those solely targeting unemployment reduction.